Optimizing Learning: A Deep Dive into Learning Discrepancies in IAIN Palopo's Islamic Education Program - Hasriadi Hasriadi; Sitti Mania; Muhammad Nur Akbar Rasyid; Dian Sanuri (South Sulawesi Education Development (SSED), 2024)
This study aims to identify and measure the gap between learning planning and its implementation in the Islamic Education Study Program IAIN Palopo field. The study employs an evaluation approach with the discrepancy model. The study involved four stages of evaluation: design, installation, process, and product. The Isaac and Michael sampling method obtained data from 948 students and 51 Islamic Education Study Program lecturers. Evaluation instruments, namely documentation, questionnaires, and interviews, are validated by expert evaluation validators. The evaluation revealed significant gaps in the availability of learning tools, human resources, facilities, infrastructure, and learning media. As per the discrepancy criterion, gap categories range from very small to large. These findings provide deep insight into the effectiveness of learning in the Islamic Education Study Program (IAIN Palopo). As a recommendation, the study suggests concrete solutions such as regular training for lecturers, the use of technology in learning, and the improvement of physical facilities to improve the quality of the learning process. The evaluation of the learning process also highlights the need to expand training and lecturer support for integrating technology into learning.